Comparison of incisional delay patterns on a rat random flap model. Issue 4 (4th July 2019) - Altınel, Dincer; Serin, Merdan; Erdem, Havva; Biltekin, Burcu; Huseyinbas, Onder; Toplu, Gaye; Kurt Yazar, Sevgi
Abstract: One of the simplest form of surgical delay can be performed by placing an incision around the flap without undermining, prior to flap elevation. In this study, we have compared the efficiency of different patterns of skin incision to improve flap survival. Twenty-eight animals were used in four groups. Incisional delay was performed prior to flap elevation in the three experiment groups. Complete incision of the three flap edges was performed in the all experiment groups with the exception of an intact skin section on the middle 1/3rd of the bilateral edges in group 1 (bilateral skin edge preserved delay: BSEPD), of a unilateral edge in group 2 (unilateral skin edge preserved delay: USEPD) and of the superior edge in group 3 (superior skin edge preserved delay: SSEPD) without any undermining. Two weeks following the delay procedure, dorsal skin flaps were raised and reinserted back to their place. The results were evaluated with the measurement of necrotic flap area, microangiographic imaging and histological evaluation. The mean percentage of necrotic flap area to whole flap area was 16.94%, 7.54%, 23.34% and 50.6% in the BSEPD, USEPD, SSEPD and control groups, respectively. In selected microangiographic images, vessels were more prominent in the delay groups. The results of the study indicate that three sided incision with an intact skin on the superior edge is not effective in providing a sufficient delay and flap survival improvement when compared to incisions with intact skin on the unilateral and bilateral edges.